Controlled Multi‐functionalization Facilitates Targeted Delivery of Nanoparticles to Cancer Cells. Issue 4 (18th December 2015) - Hudlikar, Manish S.; Li, Xiuru; Gagarinov, Ivan A.; Kolishetti, Nagesh; Wolfert, Margreet A.; Boons, Geert‐Jan
Abstract: A major objective of nanomedicine is to combine in a controlled manner multiple functional entities into a single nanoscale device to target particles with great spatial precision, thereby increasing the selectivity and potency of therapeutic drugs. A multifunctional nanoparticle is described for controlled conjugation of a cytotoxic drug, a cancer cell targeting ligand, and an imaging moiety. The approach is based on the chemical synthesis of polyethylene glycol that at one end is modified by a thioctic acid for controlled attachment to a gold core. The other end of the PEG polymers is modified by a hydrazine, amine, or dibenzocyclooctynol moiety for conjugation with functional entities having a ketone, activated ester, or azide moiety, respectively. The conjugation approach allowed the controlled attachment of doxorubicin through an acid‐labile hydrazone linkage, an Alexa Fluor dye through an amide bond, and a glycan‐based ligand for the cell surface receptor CD22 of B‐cells using strain promoted azide‐alkyne cycloaddition. The incorporation of the ligand for CD22 led to rapid entry of the nanoparticle by receptor‐mediated endocytosis. Covalent attachment of doxorubicin via hydrazone linkage caused pH‐responsive intracellular release of doxorubicin and significantly enhanced the cytotoxicity of nanoparticles. A remarkable 60‐fold enhancement in cytotoxicity of CD22 (+) lymphoma cells was observed compared to non‐ targeted nanoparticles. Abstract : Through the barricades : Controlled multi‐functionalization of nanoparticles with a cytotoxic drug, a glycan ligand for the cell surface receptor CD22, and an imaging moiety led to a remarkable 60‐fold enhancement in cytotoxicity of CD22 (+) lymphoma cells compared to non‐targeted nanoparticles.